2017
DOI: 10.1037/lhb0000208
|View full text |Cite
|
Sign up to set email alerts
|

The influence of disclosure history and body diagrams on children’s reports of inappropriate touching: Evidence from a new analog paradigm.

Abstract: We tested a new paradigm for child eyewitness research that incorporates children's disclosure histories into analog study designs. Mr. Science-Germ Detective creates meaningful touching experiences and varied patterns of preinterview disclosures by convincing children that touching in the laboratory is potentially contaminating (germy). Children (N = 287, 4 to 8 years) heard that Mr. Science could no longer touch children's skin and then participated in an educational program involving 2 attempted touches. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…As expected, interviewers’ use of visual aids in interviews did not adhere to many evidence-based recommendations and protocols: Visual aids were frequently introduced very early in the interview, most typically around the mid-point, with very few interviews restricting their use to the last stages of the interview. Extant research has typically examined aids when they are introduced following free recall (but see Dickinson & Poole, 2016), and yet we saw that aids were often introduced in the very early stages of children’s interviews in our data. In conjunction with the kinds of questioning strategies that tend to predominate when aids are used, early introduction of aids may influence children’s subsequent reporting by increasing children’s reliance on the interviewer to direct the conversation (Lamb & Brown, 2006) and by increasing the likelihood of brief, inconsistent, and possibly inaccurate responses (Brown & Lamb, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…As expected, interviewers’ use of visual aids in interviews did not adhere to many evidence-based recommendations and protocols: Visual aids were frequently introduced very early in the interview, most typically around the mid-point, with very few interviews restricting their use to the last stages of the interview. Extant research has typically examined aids when they are introduced following free recall (but see Dickinson & Poole, 2016), and yet we saw that aids were often introduced in the very early stages of children’s interviews in our data. In conjunction with the kinds of questioning strategies that tend to predominate when aids are used, early introduction of aids may influence children’s subsequent reporting by increasing children’s reliance on the interviewer to direct the conversation (Lamb & Brown, 2006) and by increasing the likelihood of brief, inconsistent, and possibly inaccurate responses (Brown & Lamb, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, in this topic, the development of psychology can bring a positive impact on increasing research and intervention [ 40 ]. Our study concludes that child maltreatment has triggered a deep concern among research authors, who performed research in various disciplines, from Government Law [ 41 , 42 ], Social Sciences [ 43 ], Criminology Penology [ 44 ], Neurosciences [ 45 ], to General Internal Medicine [ 46 , 47 , 48 ]. The authors’ keywords co-occurrence analysis has explained the level of concern about this topic.…”
Section: Discussionmentioning
confidence: 98%
“…Researchers have found that young children still struggle to understand these body diagrams as representations of self (for example, Lytle, London and Bruck, 2015). Furthermore, interviews with children involving body diagrams produce increased reports of touching (for example, Bruck, Kelley and Poole, 2016; Dickinson and Poole, 2017) and may, with younger children, come at the expense of accuracy (Bruck, Kelley and Poole, 2016).…”
Section: Communication Aids For Assessment and Investigative Interviewsmentioning
confidence: 99%